2014
DOI: 10.1039/c4ta00589a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO quantum dot/graphene nanocomposites by atomic layer deposition with high lithium storage capacity

Abstract: Uniform ZnO QDs with controllable sizes from 2 to 7 nm on graphene were synthesized. The ZnO QD/graphene nanocomposites show enhanced electrochemical properties as lithium ion battery anodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 73 publications
2
78
0
Order By: Relevance
“…[48] The anodic curves display two peaks, in which the peak at 0.51 V is related to the multi-step de-alloying process of Li-Zn alloy, and the broad peak at 1.37 V is related to the formation of ZnO according to the redox reaction between Zn and Li 2 O. [49,50] Therefore, the overall reaction process of ZnO UNPs@HPCNFs in LIBs could be described as Equations 1, 2:…”
Section: Resultsmentioning
confidence: 99%
“…[48] The anodic curves display two peaks, in which the peak at 0.51 V is related to the multi-step de-alloying process of Li-Zn alloy, and the broad peak at 1.37 V is related to the formation of ZnO according to the redox reaction between Zn and Li 2 O. [49,50] Therefore, the overall reaction process of ZnO UNPs@HPCNFs in LIBs could be described as Equations 1, 2:…”
Section: Resultsmentioning
confidence: 99%
“…For example, zinc oxide (ZnO) has attracted attention due to low cost, highly electrical conductivity (1 S cm À1 ), nontoxicity, and high theoretical capacity ($978 mAh g À1 ) [9][10][11][12]. However, a severe volume change ($228%) during the charge-discharge processes has been observed for ZnO [13]. Several approaches have been carried out to minimize the large mechanical deformation and showed improved electrochemical performance.…”
Section: Introductionmentioning
confidence: 98%
“…Wang and coworkers reported a uniform dispersion of ZnO nanoparticles ($10 nm diameter) into a porous carbon bubble host, greatly inhibiting aggregation of ZnO, accompanying with the enhanced rate capability with capacity up to 190 mAh g À1 at a current density of 49 A g À1 [15]. Furthermore, graphene has been introduced to combine with ZnO quantum dots with controllable sizes ranging from 2 to 7 nm, greatly mitigating the severe capacity fade of ZnO, which can be ascribed to the excellent mechanical properties of graphene and the ultra-small ZnO quantum dots [13]. The morphology of ZnO has been optimized for LIBs, such as nanorods and nanoflowers with prolonged cycling performance [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Most notably, Sun et al had reported for coatings of ZnO quantum dots as Li-ion battery anode material. ZnO quantum dots of various sizes from 2 to 7 nm were homogeneously coated along the curvature of graphene sheets through atomic layer deposition technique (one of the PVD method) [66]. A high reversible specific capacity of 960 mAh g À1 at a current density of 100 mA g À1 is achieved for 2 nm ZnO quantum [67].…”
Section: Coatings For Batteriesmentioning
confidence: 99%